Lung Function Test of Smokers and Non-Smokers in Ubimini Community, Emohua Local Government Area of Rivers State - Ihua, Confidence Waribo; Gam, Idawarifa Frank Cookey; Paul, John Nwolim; Dimkpa, Gospel Chimenma; Samuel, Mboi Stanley; Ekine, Dumoteinm Stephen Opuda; Obinna, Stevenson Chineme; Jones, Gloria Stanley Acra; Obia, Joyce Chisa; Amadi, Kingsley Moses (Scholars Bulletin, 2023)
The Lung function test of smokers and non-smokers was carried out using spirometer and Peak Expiratory Flowmeter in 50 subjects in Ubimini Community of Rivers State. Their ages ranged from 19.0 to 40.0 years. Mean PEFR was 524.5±80/min in smokers and 418.4 ± 96/min in non-smokers. Smokers are insignificantly lower than non-smokers. Mean 'TV was 255.8+98 in smokers and 246.4±84 in non-smokers. These results obtained showed an exceptionally increase, instead of a decrease because of the passive smokers who were exposed to cigarettes smoke most of the time while in the midst of heavy smokers but do not smoke themselves. This agreed with the findings that cigarette particles inhaled by smokers and non-smokers settle on their airway epithclia and alveoli and can elicit allergic reactions. Mean 1RV was 401.2±110 in smokers and 402.7±126 in non-smokers. Mean ERV was 323.3±150 in smokers and 424±185 in non-smokers. Mean VC was 908.4±171 in smokers and 914.3±192 in non-smokers. This showed that a non-smoker is likely to have more respiratory volume than a smoker. Mean BM1 was 40.25± 8kg/m2 in smokers and 37.55 ± 5kgm2 in non-smokers. This fact also agreed with the findings that cigarette particles inhaled by smokers and non-smokers settle on their airway epithelia and alveoli thus, can elicit allergic reactions. In comparison, PEFR is lower in smokers than in non- smokers. Thus, smokers have low flow rate when compared with non-smokers. This means that, cigarette smoking has adverse effect on lung volumes.